Rastlinsko in živalsko podobje v poeziji Svetlane Makarovič - Novak-Popov, Irena (Jezik in slovstvo, 2011)
In the early collections of poetry for adults by Svetlana Makarovič (Somrak, Kresna noč, Volčje jagode), plant and animal imagery illustrates the mood of the lyrical subject and the atmosphere, while in the later collections (Srčevec, Pelin žena, Sosed gora, Tisti čas) this imagery depicts emotions andinterpersonal relationships, as well as offences and crimes against weaker beings. By emphasising the individual, original aspects, the poet expresses disappointment and indignation at the loss of harmony with natural forces and the neglect of the sacredness of life. The specific selection of species is aligned with cosmic cycles, while the choice of plant motives creates the impression of an authority on endemic herbs with their healing and harmful effects. The poems make topical, overturn and grotesquely intensify the positive and negative semantic values that are attributed to the living world by culture, especially pre-scientific knowledge in the concept of the great chain of beings, which can easily be recognised and accepted even by estranged contemporaries.
Keywords: Makarovič, Svetlana, 1939-; Slovene literature; Slovene poetry; slovenska književnost; slovenska poezija; Slovene writers; slovenske pesnice; motif of animal; motif of plant; motiv živali; motiv rastline